INTERNAL AUDIT AND FINANCIAL REPORTING QUALITY OF QUOTED FIRMS - Amaka Elizabeth AGBATA; George EZEALA (Social Sciences and Education Research Review)
The study examines the effect of internal audit on the financial reporting quality of quoted real estate and construction firms in Nigeria. Ex-post facto research design was employed in the study. The population of the study comprised nine (9) Construction and Real Estate firms quoted on the Nigerian Exchange Group (NGX) as at 31st December 2023. The period covered was 10 years from 2014-2023. Amongst other preliminary analysis and tests, the ordinary least square regression was employed in validating the hypotheses of the study. The study found that internal audit standard has significant effect on accounting conservatism of quoted real estate and construction firms in Nigeria (P = 0.014); internal audit standard has significant effect on earning management of quoted real estate and construction firms in Nigeria (P = 0.001); internal audit standard has significant effect on accrual quality of quoted real estate and construction firms in Nigeria (P = 0.035). Consequent on the above findings, the study recommended amongst others that Real estate and construction firms should invest in comprehensive training programs for their internal auditors to ensure they are well-versed in the latest auditing standards and practices as this will improve the effectiveness of internal audits and help in the detection and prevention of accounting irregularities, thus enhancing the overall quality of financial reporting.